Analysis of efficiency of drilling equipment use in mining operations - Masaev Yuriy; Masaev Vladislav; Drozdenko Yuriy (E3S Web of Conferences, 2021)
When developing coal and ore deposits by underground method, it is necessary to carry out a large volume of preparatory mine workings using drilling and blasting operations. Minerals are found in rocks under various conditions and their physical and mechanical properties change in a wide range. Under such conditions, it is necessary to use drilling machines this different to the principle of action and structural features. The article considers geometric parameters of roc cutters, peculiarities of drilling modes, affecting energy intensity and drilling productivity in rocks with different strength coefficient.